PSIKOANALISIS HUKUM SEBUAH ALIRAN FILSAFAT HUKUM - Awaludin Marwan (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2009)
Philosophy constitutes the foundation of all branches of knowledge, with the pursuit of truth as its central objective. Within legal philosophy, truth provides the normative basis for realizing justice as the ultimate purpose of law. This article examines Jacques Lacan’s reinterpretation of the trial of Socrates to challenge the assumption that justice can be achieved solely through formal legal procedures and procedural certainty. Instead, it argues that genuine justice requires the discovery of substantive truth beyond rigid legal formalism. Employing Lacanian psychoanalysis as a philosophical and interpretive framework, the study explores the relationship between truth, subjectivity, law, and justice. It concludes that integrating psychoanalytic insights into legal philosophy enriches contemporary legal discourse by reinforcing the pursuit of substantive justice over merely procedural legality.